IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS (HOTS) IN FIQH LEARNING ASSESSMENT AT MADRASAH ALIYAH NURUL ISLAM - Siti Jamilah; Maulid Agustin (IAIN Ambon, 2025)
Abstract: Higher Order Thinking Skills (HOTS) play a crucial role in preparing students to master analytical, evaluative, and creative abilities that are essential in facing the challenges of 21st-century education. This study aims to analyze the implementation of HOTS in the assessment of Fiqh learning at Madrasah Aliyah Nurul Islam. Employing a qualitative case study design, data were collected through interviews, classroom observations, and document analysis involving the head of the madrasah, Fiqh teachers, and students. The findings reveal a shift from memorization-based assessments (LOTS) to HOTS-oriented evaluations through case studies, project-based assignments, class discussions, and structured rubrics emphasizing critical and contextual reasoning. Nevertheless, several challenges remain, including teachers’ limited capacity in developing HOTS instruments, insufficient resources, and students’ difficulties in addressing analytical questions. The novelty of this research lies in its direct exploration of HOTS-based assessments in Fiqh learning and their impact on students’ cognitive development. In conclusion, the integration of HOTS in Fiqh education contributes positively to fostering critical, analytical, and creative thinking skills, while reinforcing the relevance of Islamic education in contemporary contexts.